MENGANALISIS GAYA BAHASA METAFORA DALAM NOVEL “LASKAR PELANGI” KARYA ANDREA HIRATA - Purwati Purwati; Rianti Rosdiani; Riana Dwi Lestari; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
"Laskar Pelangi" novel is one of the communication media that is able to motivate readers through the contents of the novel. The style of language in Andrea Hirata's novel "Laskar Pelangi" plays an important role in overcoming the social gap in Indonesian society, so that the culture in Indonesia is not rampant in the world of education. The purpose of this research is to know how the Indonesian people are able to overcome the social inequalities in the society. The author intends to analyze this novel because in the novel many stories that tell the story of a person with simplicity, honesty, and tenacity. In view of the contents of the story contained in the novel, the author will try to study the style of metaphor language contained in the novel by using descriptive analytic methods.